2013
DOI: 10.1186/1471-2466-13-53
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis - a systematic review on methodology for the collection of epidemiological data

Abstract: BackgroundRecent studies suggest that the incidence of idiopathic pulmonary fibrosis (IPF) is rising. Accurate epidemiological data on IPF, however, are sparse and the results of previous studies are contradictory. This study was undertaken to gain insight into the various methods used in the epidemiological research of IPF, and to get accurate and comparable data on these different methodologies.MethodsA systematic database search was performed in order to identify all epidemiological studies on IPF after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 34 publications
0
52
0
3
Order By: Relevance
“…IPF affects ∼500 000 people in the USA and Europe [25], and its incidence appears to be increasing, as reported in multiple countries through registries and other epidemiological vehicles [6,26]. This underscores the need for effective treatments that are safe for chronic use in an older patient population; however, that goal remains elusive.…”
Section: This 6-month Open-label Clinical Trial Of Iw001 Oit In Col(mentioning
confidence: 99%
“…IPF affects ∼500 000 people in the USA and Europe [25], and its incidence appears to be increasing, as reported in multiple countries through registries and other epidemiological vehicles [6,26]. This underscores the need for effective treatments that are safe for chronic use in an older patient population; however, that goal remains elusive.…”
Section: This 6-month Open-label Clinical Trial Of Iw001 Oit In Col(mentioning
confidence: 99%
“…Ne deriva che la reale prevalenza ed incidenza dell'IPF non può essere stabilita con certezza [2]. Alcune recenti revisioni della letteratura [3,4] hanno evidenziato i diversi punti di forza e debolezza dei vari studi, del loro disegno e le principali problematiche che possono emergere, quando vengono effettuati dei confronti tra i differenti studi, rendendo pertanto difficile o impossibile giungere ad incidenze e prevalenze globali e stimare la mortalità attraverso metanalisi. L'incidenza più bassa è stata trovata in Asia, seguita dall'Europa (UE) e gli Stati Uniti (US) [2,5].…”
Section: Epidemiologia Della Ipfunclassified
“…KAUNISTO et al [28] suggested that the observed differences are probably due to various and heterogeneous methods of investigation and not to true geographical differences, as some authors suggest. KAUNISTO et al [28] also give some indications of possible reasons for the observed variability in epidemiological parameters, such as different diagnostic criteria or disease definition.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in two recent systematic reviews on IPF epidemiology [28,29], estimated mortality and morbidity rates are highly variable. KAUNISTO et al [28] suggested that the observed differences are probably due to various and heterogeneous methods of investigation and not to true geographical differences, as some authors suggest.…”
Section: Introductionmentioning
confidence: 99%